Impact of adolescent internet addiction on academic procrastination: the serial mediating role of self-control and anxiety - Wu, Zhaoliang; Xue, Li; Zhang, Yingxue; Zhan, Fengjin; Li, Hanmo; Liu, Ruici; Yang, Xi; Chen, Zi (Frontiers in Psychology, 2025)
IntroductionThis study investigated the mediating roles of self-control and anxiety in the relationship between Internet addiction and academic procrastination. Aiming to understand the psychological state of academic procrastinators and provide theoretical reference for taking effective intervention measures.MethodsData were collected from a sample of 2,421 adolescents from both a high school and university in Southwest China by convenience sampling. Measures used included the Demographic Information Questionnaire, Internet Addiction Test, Aitken Procrastination Inventory, Self-Control Scale, and Self-Rating Anxiety Scale.ResultsInternet addiction significantly negatively predicted self-control (β = −0.552, p < 0.001) and significantly positively predicted anxiety (β = 0.244, p < 0.001) and academic procrastination (β = 0.214, p < 0.001). Self-control significantly negatively predicted both anxiety (β = −0.249, p < 0.001) and academic procrastination (β = −0.430, p < 0.001). Anxiety significantly positively predicted academic procrastination (β = 0.082, p < 0.001).ConclusionThe study found that Internet addiction not only has a direct effect on academic procrastination, but also self-control and anxiety can partially mediate the relationship between Internet addiction and academic procrastination. In addition, self-control and anxiety also play a serial mediating role in the relationship between internet addiction on academic procrastination.